ANALISIS PERSEPSI PEDAGANG MENGENAI RELOKASI PASAR TRADISIONAL BOSWESEN KE PASAR MODERN RUFEI KOTA SORONG - Rokhimah Rokhimah; Andi Hasrun; Dwi Iin Kahinah; Karfin Karfin (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
The existence of a market is very helpful, not only for local and central government but also for the community. Currently the local government of Sorong City has built a modern market to relocate the existing market in Boswesen to the modern market in Rufei. This is because the sales stalls owned by traders are considered inadequate and also not neatly arranged, especially since the market is located on the side of the road so that it can disturb road users and will also disturb the people who are going to shop. However, until now traders in the Boswesen market still don't want to move to the modern market. This research aims to find out how people perceive relocation to modern markets and also why traders are still reluctant to move there. To explain this, we use a qualitative approach with data collection techniques used are interviews, observation and documentation. Based on the results of the research that has been done, the following conclusions are obtained: 1) There are two perceptions of traders regarding the relocation from the boswesen market to the modern market. There are those who agree and also those who disagree. With a percentage of 35% of traders do not agree with the relocation to modern markets and 65% of traders agree with the relocation. 2) There are several reasons why traders do not want to move to the modern market, namely because only some traders have moved to the modern market and some of them live in the Boswesen market, the location is far away and the selling stalls in the modern market are smaller in size, and also the costs they will incur in the modern market are greater than those in the Boswesen market.